2019
DOI: 10.1177/1129729819861187
|View full text |Cite
|
Sign up to set email alerts
|

In-line filtration reduced phlebitis associated with peripheral venous cannulation: Focus on cost-effectiveness and patients’ perspectives

Abstract: Background: In a previous trial, in-line filtration significantly prevented postoperative phlebitis associated with short peripheral venous cannulation. This study aims to describe the cost-effectiveness of in-line filtration in reducing phlebitis and examine patients’ perception of in-hospital vascular access management with and without in-line filtration. Methods: We analysed costs associated with in-line filtration: these data were prospectively recorded during the previous trial. Furthermore, we performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Post-mortem studies have demonstrated the presence of plastic and glass particles in the vessels and lungs of critically ill patients, resulting in mechanical blockage of the microcirculation, local inflammation, and tissue granuloma 2 , 3 . Several studies have demonstrated the capability of intravenously infused particles to induce endothelial damage, inflammation, and immune system activation 4 , 5 . Particle retention positively affects surgical and critically ill patients, especially when treated with high amounts of intravenous fluids and drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-mortem studies have demonstrated the presence of plastic and glass particles in the vessels and lungs of critically ill patients, resulting in mechanical blockage of the microcirculation, local inflammation, and tissue granuloma 2 , 3 . Several studies have demonstrated the capability of intravenously infused particles to induce endothelial damage, inflammation, and immune system activation 4 , 5 . Particle retention positively affects surgical and critically ill patients, especially when treated with high amounts of intravenous fluids and drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In-line filters are disposable products placed inside the intravenous line to retain particles and prevent unintentional administration to the patient through the vascular access device. Villa et al demonstrated that in-line filters significantly reduce endothelial damage in surgical patients 4 , 5 . Furthermore, Sasse et al observed a significant reduction in the development of systemic inflammatory disorders and multiple organ dysfunction in a cohort of intensive care unit (ICU) patients when in-line filtration was applied to prevent the infusion of intravenous particles during the ICU stay 1 .…”
Section: Introductionmentioning
confidence: 99%